PENGARUH ARUS KAS OPERASI, PROFITABILITAS, DAN SALES GROWTH TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Nuraini Anis Arifah; Leny Suzan (Yayasan Akrab Pekanbaru, 2018)
This study aims to find out how the influence of operating cash flows, profitability and sales growth on dividend policy proxied by Dividend Payout Ratio (DPR) at mining companies listed on the BEI period 2012-2016. The data used in this study were obtained from the financial statements. The population in this study is a mining sector company listed on the BEI. Sample selection technique used is purposive sampling and obtained 6 samples within 5 years so that obtained 30 sample unit of mining company period 2012-2016 period. Data analysis method in this research is panel data regression by using Software Eviews 9.0. Based on the results of data processing shows that simultaneously operating cash flow, profitability and sales growth have a significant effect on dividend policy. While partially, operating cash flow has no significant effect on dividend policy, profitability has a significant effect on dividend policy and sales growth negatively affect dividend policy. Based on the results of this study, a company that wants to distribute dividends should pay attention to sales growth, this is because large sales growth tends to allocate funds for the expansion of the company compared with distributing dividends. Keywords: Operating Cash Flow, Profitability, Sales Growth, Dividend Policy.